Claire Swierczek: capstone - Swierczek, Claire, artist (Colorado State University. Libraries, 2019)
The artist's statement: With my passion for illustration and character design, I combine typography and art together to create content that is both visually engaging and aesthetically pleasing. The ability to portray someone's life and their experiences beyond my own scope has always been fascinating to me and is what motivated me to begin pursuing illustration a decade ago. Character art and interactions give me the ability to see past my own boundaries and to create experiences I might not be able to achieve on my own, which is both a great inspiration and a key element to my artistic pursuit as a whole. My area of expertise lies largely with character design and finding ways to incorporate someone's story - their personality, history, hopes, or even fears - into a drawing. I use traditional pencils and pens for my initial sketching phase which gives my lines a looser, more organic quality that lends itself to an ultimately more satisfying form that I then use as a base for my finished digital pieces using programs like Photoshop or Clip Studio Paint. A genuine sense of movement is important to my art and what I believe truly breathes life into a piece. I've worked with several individual clients in the past illustrating their original characters and scenes, ranging from fictional lawyers and baristas to Dungeons and Dragons characters, and it is through my own carefully cultivated style of sharp lines and smooth curves as well as a general passion for character-driven art that I've found my own artistic voice and place within the illustration community.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design